Adoption of Artificial Intelligence in Marketing Management and Its Implications for Customer Experience Enhancement (International Journal of Economics Management and Social Science, 2026)
The integration of Artificial Intelligence (AI) in marketing management has revolutionized how organizations interact with customers and deliver value. This study examines the adoption of AI technologies in marketing management and their implications for enhancing customer experience. Through a comprehensive literature review and analysis of current industry practices, this research identifies key AI applications including predictive analytics, chatbots, personalization engines, and sentiment analysis. The findings reveal that AI adoption significantly improves customer experience through enhanced personalization, real-time engagement, predictive customer service, and data-driven decision making. However, challenges such as data privacy concerns, implementation costs, skill gaps, and ethical considerations persist. The study proposes a framework for successful AI adoption in marketing that encompasses strategic alignment, technological infrastructure, organizational readiness, and customer-centric design. This research contributes to the growing body of knowledge on AI in marketing and provides practical insights for organizations seeking to leverage AI for competitive advantage and superior customer experience. Keywords: Artificial Intelligence, Marketing Management, Customer Experience, Personalization, Digital Transformation, Predictive Analytics